Perancangan User Interface / Experience Aplikasi ABC Menggunakan Metode Kansei Engineering - Anwar, Faris Asiful; Sodik, Anwar (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2025)
This study aims to improve the quality of the user interface (UI) and user experience (UX) of the ABC application using the Kansei Engineering approach. Through data collection from 30 respondents, multivariate statistical analysis such as Coefficient Correlation Analysis, Principal Component Analysis, and Partial Least Square were used to translate user emotions into design elements. The results of the study produced design recommendations based on the concept of the emotion "Meyakinkan" which includes 21 main categories of UI elements. Initial SUS testing showed a score of 49 (Marginal Low), while testing on the prototype produced a score of 74 (Marginal High), indicating a significant increase in application usability. Thus, the Kansei Engineering approach has proven effective in designing UI/UX based on user emotional preferences.